Entrepreneurial activities among single mothers in Johor - Abu Bakar, Thuaibah @ Suaibah; Omar, Rozeyta; Panatik @ Abdul Rahman, Siti Aisyah; Muktar, Syahrizatul Noorizwan; Md. Ali, Azlah; Jamil, Rossilah; Md. Som, Hishamuddin; Yusof, Mohd. Azizi (Universiti Teknologi Malaysia, 2006)

(untitled)
Entrepreneurial motivation and passion are considered important elements in the recent development of entrepreneurial activities. Both motivation and passion are needed as a means to attain a greater height especially in an environment that requires a lot of concerted ideas and commitment. This study is intended to find out the dimensions that would help sustaining the interest of single mothers into entrepreneurship and later to prove the role of motivation and passions in explaining entrepreneurial success among single mothers. The findings is supported by a research survey, using cluster sampling technique that have been carried out in six (6) states in Malaysia (representing East, West, North and South of Peninsular Malaysia together with Sabah or Sarawak representing East Malaysia). The results of this study suggest that a motivational role does have significant influence on entrepreneurial passion which is later used to explain entrepreneurial success.